Implementasi Algoritma Apriori Untuk Mencari Relasi Pada Transaksi Pembelian Alat-Alat Kesehatan - Berta Rohana Br Purba; Nelly Astuti Hasibuan; Guidio L Ginting; Suginam Suginam (JURIKOM (Jurnal Riset Komputer), 2018)
Implementation of data mining in the supply of health equipment that affects the quality of hospital services, excessive inventory will pose some risks, such as theft or enormous storage costs because it requires the accurate recording to address the supply of medical devices. A priori algorithm is a data gathering with association rule to determine the associative relation of an item through the mechanism of calculating the support and confidence of an item relation, the apriori algorithm is suitable to be applied when some items of one item relationship in the health field are analyzed and analyzed and the determination of the purchase health equipment.